Analisis Perbandingan Output Daya Panel Surya Monokristalin dengan dan tanpa Reflektor Cermin - Harahap, Basyaruddin Ismail; wanatirta, Bimbi Adytia; alajuri, M. Hasbi Sidqi; Bonardo, Doli; Bavitra, Bavitra (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to analyze the comparison of the power output of monocrystalline solar panels with and without the use of mirror reflectors. The utilization of solar energy continues to grow, but the efficiency of solar panels highly depends on light intensity. The use of mirror reflectors is proposed as a method to increase the irradiation received by the panels. A quantitative experimental method was used, involving two identical configurations of monocrystalline solar panels: one without a reflector (control) and one with a mirror reflector. Voltage, current, temperature, and power data were collected every minute from 08:00 to 14:00 WIB using a microcontroller-based data acquisition system. The average results show an increase in the output power of the panel with a reflector (1.75W) compared to without a reflector (1.58W), although the temperature of the panel with a reflector is slightly higher. Analysis of variance (ANOVA) shows that the F-value (15206.12) far exceeds the F-table (2.012305) with a p-value approaching zero (0). These results statistically prove the existence of a significant difference in power output between the two configurations. Thus, it can be concluded that the use of mirror reflectors substantially increases the power output of monocrystalline solar panels, making it an effective strategy for optimizing the performance of photovoltaic systems.